2005
DOI: 10.1159/000089318
|View full text |Cite
|
Sign up to set email alerts
|

Turner Syndrome, Insulin Sensitivity and Growth Hormone Treatment

Abstract: Mild insulin resistance appears to be an early metabolic defect in girls with Turner syndrome (TS). Impaired glucose tolerance has been reported in 10–34% of patients with TS, and type 2 diabetes mellitus is 2–4 times more common and occurs at a younger age in girls with TS than in the general population. In a mixed longitudinal and cross-sectional study, we analysed carbohydrate tolerance and insulin sensitivity in 46 children and adolescents with TS who reached their final height after long-term treatment (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…In accordance with our findings, several other studies found that insulin sensitivity decreased during GH therapy [6,9,26,27,28]. These studies showed that after discontinuing GH therapy, insulin sensitivity indices either returned to pre-treatment levels [27], or decreased to values just above baseline but comparable with those of healthy post-pubertal girls [29]. In our study, the indices returned to pretreatment levels, confirming the reversibility of the effect of GH on insulin sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with our findings, several other studies found that insulin sensitivity decreased during GH therapy [6,9,26,27,28]. These studies showed that after discontinuing GH therapy, insulin sensitivity indices either returned to pre-treatment levels [27], or decreased to values just above baseline but comparable with those of healthy post-pubertal girls [29]. In our study, the indices returned to pretreatment levels, confirming the reversibility of the effect of GH on insulin sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…During the last decade many studies showed growth hormone (GH) treatment as safe and effective for growth promotion in TS. Table 2 presents the results of growth therapy and indicates positive, negative and neutral determinants of therapy effectiveness as well as consequences and side effects of hormonal therapy in the analysed articles (4,5,7,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50).…”
Section: Growth and Growth Therapy And Consequencesmentioning
confidence: 99%
“…Elevated levels of IGF1 should be avoided in view of the potential long-term adverse effects. Also careful monitoring for benign intracranial hypertension, scoliosis, slipped capital femoral epiphysis, body proportion, abnormal glucose tolerance and reduced insulin sensitivity is recommended (41,43,50,107).…”
Section: Growth In Transition Timementioning
confidence: 99%
“…However, there is a worth mentioning aspect of the present study's design. Previous studies showed increased metabolic risk in TS girls/woman in comparison to the healthy, normal-weight patients [3,[17][18][19][20]. The present study is the first to date comparing markers of the metabolic risk in patients with TS on growth hormone treatment and obese peers.…”
Section: Discussionmentioning
confidence: 54%